Producer Behavior in Facing a 12% VAT Increase - Nihayatul Umniyah Salsabila; Amin Wahyudi (al-Afkar, Journal For Islamic Studies, 2025)
The increase in the Value Added Tax (VAT) rate to 12%, effective January 2025, based on Law Number 7 of 2021 concerning the Harmonization of Tax Regulations (HPP Law), has had a significant impact on production and consumption behavior in Indonesia. This increase impacts producers facing increased production costs, particularly those related to raw materials subject to VAT. Producers are required to adjust their production strategies, including price adjustments, increased operational efficiency, and product diversification. Meanwhile, consumers face the impact of rising prices for goods and services, which impacts purchasing power, particularly among low- and middle-income groups. In response to this VAT rate increase, the government is expected to implement consumer protection policies, such as subsidies for basic goods and social assistance, to maintain purchasing power and prevent further economic inequality. This study explores the relationship between taxation and production behavior and suggests strategies that producers can adopt to maintain competitiveness in an increasingly competitive market.